2011
DOI: 10.2989/1814232x.2011.637356
|View full text |Cite
|
Sign up to set email alerts
|

The Marine Mammal Programme at the Prince Edward Islands: 38 years of research

Abstract: The Marine Mammal Programme (MMP) conducts research on pinnipeds and killer whales at Marion Island, Prince Edward Islands, under the auspices of the Mammal Research Institute, Department of Zoology and Entomology, University of Pretoria. The early history of the MMP is described, emphasizing the contributions in subsequent years, ending with current research. The setting up of long-term studies such as the mark-resighting of southern elephant seals Mirounga leonina was implemented in 1983. The varying fates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 119 publications
(99 reference statements)
0
25
0
Order By: Relevance
“…Fur seal populations at Marion Island are closely monitored as part of the Marion Island Pinniped Monitoring Programme (Bester et al 2011). The leucistic individuals described here were all observed at Landfall Beach, MI (Fig.…”
Section: Oosthuizenmentioning
confidence: 99%
See 1 more Smart Citation
“…Fur seal populations at Marion Island are closely monitored as part of the Marion Island Pinniped Monitoring Programme (Bester et al 2011). The leucistic individuals described here were all observed at Landfall Beach, MI (Fig.…”
Section: Oosthuizenmentioning
confidence: 99%
“…(Bonner 1968). The pup weaned successfully in April 2011, but was subsequently never resighted despite extensive field researcher presence through intensive multi-species seal research at MI (de Bruyn et al 2007, Bester et al 2011. A leucistic adult female was recorded during the breeding seasons of 2006/2007, 2007/2008, 2009/2010, 2010/2011 and 2011/2012 at Landfall Beach ( Fig.…”
mentioning
confidence: 99%
“…Considering the extraordinarily high observer effort of marine mammal field personnel at Marion Island over the past three-and-ahalf decades (Bester et al 2011), the observation reported by de Bruyn et al (2008) Determining the drivers of the unusual behaviour described here is nearly impossible.…”
Section: Discussionmentioning
confidence: 87%
“…Of course, technological improvements allow for answering new questions, and therefore require new deployments of suitable instruments, and in some cases ongoing deployments of appropriate devices are pursued in the context of long-term monitoring programmes (e.g. Bester et al 2011). However, there is a substantial amount of marine mammal biologging data among researchers across the world that could support new research.…”
Section: Scientific Impactmentioning
confidence: 99%